SIADH as the initial manifestation of acute intermittent porphyria: A case report - S, Tony K; Joshi, Rakhee; Chaudhari, Pradnya; Abraham, Reshma; Joshi, Nachiket; Mulye, Adwait; Wankhede, Abhinav (Indian Journal of Case Reports, 2021)
Acute intermittent porphyria (AIP) is a rare autosomal dominant and the most severe form of the inherited hepatic porphyrias, affecting mainly young women. We present the case of an 18-year-old female who presented with severe abdominal pain, purple urine, autonomic dysfunction, and severe hyponatremia, seizures on further evaluation came out to be a case of AIP. This case report is a reminder to keep AIP among the differentials in young female patients with a classic constellation of abdominal urine discoloration syndrome of inappropriate secretion of antidiuretic hormone and autonomic dysfunction.